2022
DOI: 10.3390/jcm11164702
|View full text |Cite
|
Sign up to set email alerts
|

Can Leukotriene Receptor Antagonist Therapy Improve the Control of Patients with Severe Asthma on Biological Therapy and Coexisting Bronchiectasis? A Pilot Study

Abstract: Introduction: Asthma and bronchiectasis appear to be two related diseases and in their complex inflammatory interaction, the cysteinyl leukotriene/cysteinyl leukotriene receptor 1 (cysLT/cysLTR1) axis appears to play an important role given its involvement also in the neutrophilic pathway. To our knowledge, few studies have been conducted so far to evaluate the role of the leukotriene cysLT/cysLTr1 axis in the management of clinical and inflammatory outcomes within a population of patients with severe asthma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…In our group, anti-IgE therapy led to a reduction in the need for systemic corticosteroids and a reduction in the number of exacerbations, as well as a gradual improvement in fitness and a return to physical activities, but the persistent overweight from the period before the initiation of anti-IgE therapy seems to be one of the possible reasons for the higher risk of CVD in some patients, in addition to the severity of the disease. The effect of LTRA therapy on improving control in patients with severe asthma on biological therapy was investigated by Quaranta et al [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our group, anti-IgE therapy led to a reduction in the need for systemic corticosteroids and a reduction in the number of exacerbations, as well as a gradual improvement in fitness and a return to physical activities, but the persistent overweight from the period before the initiation of anti-IgE therapy seems to be one of the possible reasons for the higher risk of CVD in some patients, in addition to the severity of the disease. The effect of LTRA therapy on improving control in patients with severe asthma on biological therapy was investigated by Quaranta et al [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another unplanned post hoc analysis of a randomised, double‐blind, controlled study also suggested that 6‐month treatment with inhaled fluticasone propionate in adults with bronchiectasis significantly improved quality of life with a trend of lower exacerbation rate among those with a blood eosinophil count ≥3% or ≥150 cells/μL compared with control 21 . Nonetheless, post hoc analysis of another randomised, double‐blind, parallel‐group trial of 40 patients with bronchiectasis revealed no significant change in quality of life after 6 months of inhaled budesonide treatment in the subgroup with baseline blood eosinophil count of at least 3% and 150 cells/μL 22 …”
Section: Discussionmentioning
confidence: 92%
“…21 Nonetheless, post hoc analysis of another randomised, double-blind, parallel-group trial of 40 patients with bronchiectasis revealed no significant change in quality of life after 6 months of inhaled budesonide treatment in the subgroup with baseline blood eosinophil count of at least 3% and 150 cells/μL. 22 The role of ICS in preventing bronchiectasis exacerbation remained controversial. Despite the evidence from earlier reports, this was challenged by subsequent Cochrane review and European guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In different types of asthma included in the study, like aspirin-exacerbated, elderly asthma, smoking asthma, obesity associated asthma along with asthma comorbid with allergic rhinitis, LTRA therapy proved to be advantageous because of the reduction of FeNO biomarker. LTRA therapy acts on both eosinophilic and neutrophilic inflammatory pathway to control asthma exacerbation [11].…”
Section: Resultsmentioning
confidence: 99%